EVALUASI PENDAPATAN PELABUHAN (TERMINAL) MELALUI PENDEKATAN REGRESI SHIP TURNAROUND TIME - , Muhammad Aftoni; , Dr. Wakhid Slamet Ciptono, MBA., MPM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ship turnaround time and container throughtput are the objective of a port (terminal) without ignored potentially damage cargo while doing loading and/or discharge (unloading) containers from/to ship. This research was taken places on 3 (three) terminal operators in Port of Tanjung Priok. This research aims to indentify which container terminal that has strong correlation with loading and/or discharge (unloading) containers from/to ship. Quay crane is the main facility for loading and/or unloading container from/to ship. Otherwise, all the port facilities must works harmonically